Premio del Golfo 1985 - Biennale d'Arte Editrice La Spezia 1985; Menna, Filiberto; Occhipinti, Carlo (La Spezia : Biennale d'Arte Editrice, 1985)
Alfano, Carlo ; Bartolini, Luciano ; Bertocci, Carlo ; Boero, Renata ; Carena, Antonio ; Coletta, Pietro ; Dadamaino ; De Nevi, Paolo ; Fabiani, Mauro ; Gilardi, Pietro ; Griffa, Giorgio ; Lista, Pietro ; Mariani, Carlo M. ; etc.
Premio del Golfo 1985, Biennale d'Arte Editrice, La Spezia, Novembre 1985 - Gennaio 1986
boek